Analysis of Index Decomposition of Capture Ratio of Total Annual Runoff Volume in Sponge Cities - WEN Dawen; YANG Jiantao; WANG Sen; LIU Jin; WANG Bin (Renmin Zhujiang)
One of the important goals of sponge city construction is to reduce the discharge of rainwater runoff and the local consumption and utilization of rainwater runoff within the plot.The discharge volume of rainwater runoff is reflected by the capture ratio of the total annual runoff volume.How to scientifically and reasonably determine the capture ratio of total annual runoff volume has been the main exploration content in the process of sponge city construction in recent years.This study took the Guangzhou Science and Education City area as an example,utilized the data of the underlying surface and drainage pipe network of the plot,and used the volumetric method to decompose the capture ratio of total annual runoff volume.At the same time,the Infoworks ICM model was used to simulate and verify the rationality of the decomposition of the capture ratio of the total annual runoff volume for each plot.The results show that after the development and construction of each plot according to the planned capture ratio of the total annual runoff volume,the drainage pipe network of the plot meets the 10-year return period of design.Under the condition of precipitation once in 100 years,there is water accumulation in some areas,but no waterlogging occurs.Research has shown that the capture ratio of the total annual runoff volume of each plot determined through decomposition can be used to guide the development and construction of the plot.The construction of sponge cities can effectively reduce rainwater discharge and enhance regional disaster prevention and reduction capabilities.